Use of Emerging Technologies in Disaster Management - Harsh Yadav (International Journal of Pollution: Prevention & Control, 2025)
India, one of the most disaster-prone nations, faces increasing challenges from natural and man- made disasters. To address these risks, the country has developed a multi-tiered institutional framework, led by the National Disaster Management Authority (NDMA) and supported by state and local bodies. While these efforts provide a strong foundation, the integration of emerging technologies is reshaping disaster management. Technologies like Artificial Intelligence (AI), drones, and advanced early warning systems enhance disaster prediction, enable faster response, and support effective resource management. Despite their benefits, the widespread adoption of these tools is hindered by economic constraints, regulatory issues, and a lack of skilled operators. This paper examines the impact of these technologies on disaster preparedness and response, identifies challenges, and proposes solutions such as strengthening regulations, fostering innovation through public-private partnerships, and investing in training and capacity building. The study emphasizes that adopting advanced yet sustainable technologies can significantly reduce disaster impacts and enhance community resilience. This paper overall explores the application of advanced technologies in improving disaster management processes. It discusses various cutting-edge tools and systems, such as AI, IoT, drones, and GIS, highlighting their roles in risk assessment, disaster preparedness, response, and recovery. The document emphasizes the transformative potential of these technologies in minimizing disaster impacts and enhancing resilience.
Keywords: Artificial Intelligence (AI); capacity building; disaster management; drones and uavs; early warning systems (EWS); emerging technologies; resilience